Soils of andijan region and practical value of using them and problems of protection - М.Маmajonov (Universitas Muhammadiyah Sidoarjo, 2019)
This article covers the types of soils, their biological, chemical, physical properties, grain properties, geographical distribution, their use and protection in the field of agriculture in the Andijan region. The article provides a separate analysis of the soil in the districts of the region and provides information on their characteristics